Trump, Obama, Bush: Impacts of Presidential Elections on College Student Mental Health. Issue 1 (2nd January 2023) - Merrill, Brett M.; Vogeler, Heidi; Kirchhoefer, Jessica; Tass, Shannon; Erekson, Davey; Beecher, Mark; Worthen, Vaughn; Hobbs, Klint; Boardman, R. D.; Bingham, Jennie; Bailey, Russell J.; Cox, Jonathan C.; et al.
ABSTRACT: Research, media sources, and polls have identified negative effects associated with presidential elections. The aim of this research was to investigate associations between US presidential election results and mental health outcomes in university students. This investigation consisted of two independent studies. Study 1 analyzed data collected between the years 2000 and 2016 from students who utilized counseling services (N = 32, 506) at a large, private, conservative institution in the western United States. Study 2 analyzed data collected between the years 2010 and 2016 from over 100 university counseling centers across the United States. Upon analyzing the quantitative and qualitative data, the results did not support the findings that presidential elections negatively impact the mental health outcomes of students who receive university counseling services. Furthermore, there was no detectable increase in student distress regardless of election year, age, ethnicity, gender, religion, relationship status, sexual orientation, geographic region, citizenship, and first-generation student status.